Gamma interferon responses to proteome-determined specific recombinant proteins in cattle experimentally- and naturally-infected with paratuberculosis. (October 2017) - Hughes, Valerie; McNair, Jim; Strain, Samuel; Barry, Claire; McLuckie, Joyce; Nath, Mintu; Caldow, George; Stevenson, Karen
Abstract: Johne's disease (JD), is a fatal enteritis of animals caused by infection with Mycobacterium avium subspecies paratuberculosis ( Map ). Diagnosis of subclinical JD is problematic as test sensitivity is limited. Th1 responses to Map are activated early, thus detection of a cell-mediated response, indicated by measuring interferon gamma (IFN-γ) stimulated by mycobacterial antigens, may give the first indication of sub-clinical infection. Crude extracts of Map (PPDJ) have been used to detect the cell-mediated response in infected cattle. More specific, quantifiable antigens may improve test specificity and reproducibility. Map -specific proteins, MAP_3651c and MAP_0268c, raised a cell-mediated immune response in sub-clinically infected sheep. Results presented in this manuscript demonstrate these proteins elicit a cell-mediated response in experimental and natural infections of cattle. Individual ranked IFN-γ responses of experimentally infected calves to PPDJ showed a high, statistically significant association with ranked responses of recombinant Map antigens. Responses of infected animals were higher than the control group. Threshold values determined using data from an experimental infection were applied to naturally infected animals. Some animals exhibited responses above these threshold values. Responses to MAP_3651c on a farm categorised as high-risk for JD showed strong evidence (P < 0.001) that responses were significantly different to lower-risk farms. The IGRA test may prove to be an additional tool for the diagnosis of JD, and inclusion of specific antigens a refinement however, understanding and interpretation of IGRA results remain challenging and further investigation will be required to determine whether the IGRA test can detect exposure and hence predict clinical JD. Highlights: MAP_0268c and MAP_3651c stimulate the cell-mediated response of Map infected cattle. Experimental infections were detected using recombinant antigens derived from Map . Animals with naturally acquired Map infections responded to recombinant antigen. Tests of cattle with varying risk for Map infection were significantly different.